STATUS KUALITAS PERAIRAN UMUM DAN AIR TANAH DI WILAYAH JAKARTA - Sachoemar, Suhendar I.; Wahjono, Heru Dwi (Jurnal Air Indonesia, 2007)
The environment and water quality status of the open waters of the rivers and lake including ground water surround DKI Jakarta was evaluated on the base of the data collected by local government of the environmental agency of DKI Jakarta (BPLHD) period of 2004. The result shows that water quality of those open waters has degraded due to the impact of the domestic and industrial waste that flowing through the rivers. The DO, total suspended solid (TSS), ammonia, organic matter, BOD and COD of the open waters in general have more than intemperate of the environmental standard of the water quality for drinking, fisheries, animal husbandry and industrial need. While the ground water has degraded due to the increasing of the Fe, Mn and detergent. To eliminate and minimize the degradation of the water quality of the open waters and ground water surround Jakarta, strict regulation should be established following the regular monitoring of the whole area of the open and ground waters. Katakunci : Kualitas Perairan Umum, Sungai, Situ, Air Tanah, DKI Jakarta.